2022
DOI: 10.1111/bph.15913
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarein attenuates atopic dermatitis by selectively inhibiting transient receptor potential vanilloid 3 channels

Abstract: Background and Purpose Atopic dermatitis (AD) is one of the most common chronic inflammatory cutaneous diseases with unmet clinical needs. As a common ingredient found in several medicinal herbs with efficacy on cutaneous inflammatory diseases, Scutellarein (Scu) has been shown to possess anti‐inflammatory and anti‐proliferative activities. We aimed to evaluate the therapeutic efficacy of Scu against AD and its underlying molecular mechanism. Experimental Approach Efficacy of Scu on AD was evaluated in 2,4‐din… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…It has been shown that the suppression of overactive TRPV3 channel function through gene silencing or the use of channel inhibitors reduces skin lesions ( 30 , 31 ). We, therefore, generated a mouse model of dorsal skin inflammation induced by topical applications of skin sensitizer DNFB at a concentration of 0.5% once a day on the first day and subsequent 0.2% DNFB once a day for 2 days ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the suppression of overactive TRPV3 channel function through gene silencing or the use of channel inhibitors reduces skin lesions ( 30 , 31 ). We, therefore, generated a mouse model of dorsal skin inflammation induced by topical applications of skin sensitizer DNFB at a concentration of 0.5% once a day on the first day and subsequent 0.2% DNFB once a day for 2 days ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is functionally related to apigenin [ 41 ]. Recent research has focused on scutellarein owing to its interesting bioprotective properties, including anticancer, antiproliferative and antioxidant activities [ 42 ] ( Table 1 ). Interestingly, being a flavone, its structure is based upon the backbone of -phenylchromen-4-one (2-phenyl-1-benzopyran-4-one) [ 43 ].…”
Section: Sources and Chemistry Of Scutellaria Flav...mentioning
confidence: 99%
“…Therefore, this approach helps determine the concentrations and forms of such compounds in plasma and tissue. In addition, most flavonoids tend to bind sugars as b-glycosides, which further determine their absorption directly from the small intestine or through the colon [ 42 ]. Interestingly, before absorption, the dietary flavonoids must be released by chewing or digestion via digestive juices (gastrointestinal tract) followed by the action of microorganisms in the colon.…”
Section: Absorption and Metabolism Of Scutellaria ...mentioning
confidence: 99%
“…For instance, T636's contact with Y594 is the primary edge between the Pore and S5 helices and is directly adjacent to the S6 pi bulge [51]. Mutating T636 to serine resulted in a hyperactive mutant [52] and this same position is known to be a binding site for the inhibitor scutellarin [53]. A highly central inter-protomer edge passes through M572 and F592, between the PC6 cluster and region associated with Olmsted Syndrome.…”
Section: Edge Betweenness Centrality Identifies Allosteric Pathwaysmentioning
confidence: 99%